2020
DOI: 10.1002/aet2.10462
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of the Cumulative Experiences of Emergency Medicine Residents in the Pediatric Emergency Department

Abstract: Objectives: Most children seeking emergency care are evaluated in general emergency departments (EDs). The cumulative pediatric clinical experiences of emergency medicine (EM) residents are largely unknown. This study examined EM resident pediatric clinical experience through the lens of the Accreditation Council for Graduate Medical Education requirements and the Model of the Clinical Practice of Emergency Medicine. Methods: Retrospective, observational study of the cumulative clinical experience of two class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Leaders in PEM have long identified the need for a standardized longitudinal PEM curriculum for EM trainees. [6][7][8][9][10][11][13][14][15]18,19,22,24,[43][44][45] We sought to create and implement a comprehensive and pedagogically sound PEM curriculum for our EM residents. The curriculum pilot was well received, and we were able to detect early evidence of program effectiveness.…”
Section: Reflec Tive Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Leaders in PEM have long identified the need for a standardized longitudinal PEM curriculum for EM trainees. [6][7][8][9][10][11][13][14][15]18,19,22,24,[43][44][45] We sought to create and implement a comprehensive and pedagogically sound PEM curriculum for our EM residents. The curriculum pilot was well received, and we were able to detect early evidence of program effectiveness.…”
Section: Reflec Tive Discussionmentioning
confidence: 99%
“…5 Nevertheless, EM residents experience limited exposure in terms of breadth and acuity of pediatric presentations. [6][7][8][9][10][11] Additionally, the American Board of Emergency Medicine (ABEM) Model of Clinical Practice references age among "modifying factors" affecting patient management, which may minimize the distinctiveness of important PEM diagnoses. 12,13 Addressing these educational shortcomings, the 2018 Academic Emergency Medicine (AEM) Consensus Conference "Advancing Pediatric Emergency Medicine Education" concluded that currently there is "no clearly defined core PEM curriculum that unifies and drives the learning process" for trainees.…”
Section: Need For Innovationmentioning
confidence: 99%
See 3 more Smart Citations